2014
DOI: 10.1038/cdd.2014.58
|View full text |Cite
|
Sign up to set email alerts
|

Dominant-negative function of the C-terminal fragments of NBR1 and SQSTM1 generated during enteroviral infection

Abstract: Coxsackievirus infection induces an abnormal accumulation of ubiquitin aggregates that are generally believed to be noxious to the cells and have a key role in viral pathogenesis. Selective autophagy mediated by autophagy adaptor proteins, including sequestosome 1 (SQSTM1/p62) and neighbor of BRCA1 gene 1 protein (NBR1), are an important pathway for disposing of misfolded/ubiquitin conjugates. We have recently demonstrated that SQSTM1 is cleaved after coxsackievirus infection, resulting in the disruption of SQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 40 publications
(49 reference statements)
3
45
0
Order By: Relevance
“…We investigated the similarity between this cleavage of SQSTM1 by EV-D68 and the cleavage seen by Shi et al (2014) and obtained SQSTM1-expressing plasmids from the authors. The first plasmid was a SQSTM1 wild-type plasmid, originally sourced from Yu et al (2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated the similarity between this cleavage of SQSTM1 by EV-D68 and the cleavage seen by Shi et al (2014) and obtained SQSTM1-expressing plasmids from the authors. The first plasmid was a SQSTM1 wild-type plasmid, originally sourced from Yu et al (2009).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work by our group has demonstrated that poliovirus 1 (PV) uses acidic amphisomes to promote virus replication and maturation (Richards and Jackson, 2012). Coxsackievirus B3 induces the autophagic pathway but may inhibit degradation of autophagic cargo (Alirezaei et al, 2015; Shi et al, 2014; Wong et al, 2008). We report here that EV-D68 induces autophagy signaling to benefit its replication and manipulates the autophagosomal SNAREs.…”
Section: Introductionmentioning
confidence: 99%
“…54,55 HeLa cell lysates (50 μg) were incubated with various concentrations of purified CVB3 2A, 3C, or 3C mutant as indicated in a cleavage reaction buffer (20 mM HEPES (pH 7.4), 150 mM KOAc and 1 mM DTT) at 37˚C for different times as previously described. 20,51 The reaction was stopped by addition of 6 × SDS-PAGE sample buffer and TDP-43 cleavage was assessed by western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…18 However, the role of TDP-43 in virus-induced diseases has not been studied. Recent evidence suggests that CVB3-induced pathogenesis resembles the pathological features of neurodegenative disease, that is, abnormal accumulation of insoluble, misfolded protein aggregates (also known as proteinopathies), 3,19,20 prompting us to hypothesize that dysregulation of TDP-43 during CVB3 infection plays a role in viral pathogenesis, and probably viral infectivity as well. …”
mentioning
confidence: 99%
“…They function as autophagy receptors targeting ubiquitinated proteins to autophagosomes for degradation [186][187]191]. It was recently reported that both p62 and Nbr1 are cleaved following CVB3 infection, through the action of CVB3-encoded protease 2A and 3C [192,193]. It was further shown that such cleavage leads to disrupted selective autophagy and results in the impaired clearance of ubiquitin aggregates [193].…”
Section: • • Host Cell Eating In Coxsackieviral Infectionmentioning
confidence: 97%